2022
DOI: 10.1080/15384101.2022.2049157
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a five-gene signature deriving from the vacuolar ATPase (V-ATPase) sub-classifies gliomas and decides prognoses and immune microenvironment alterations

Abstract: Aberrant expression of coding genes of the V-ATPase subunits has been reported in glioma patients that can activate oncogenic pathways and result in worse prognosis. However, the predictive effect of a single gene is not specific or sensitive enough. In this study, by using a series of bioinformatics analyses, we identified five coding genes (ATP6V1C2, ATP6V1G2, TCIRG1, ATP6AP1 and ATP6AP2) of the V-ATPase that were related to glioma patient prognosis. Based on the expression of these genes, glioma patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…ATP6AP1 gene mutations are involved in congenital disorders of glycosylation (CDG) and affect multiple organ systems, including immunodeficiency and cognitive impairment [ 36 , 37 , 38 ]. One study recently showed that a risk signature including ATP6AP1 could reasonably predict the prognosis and immune microenvironment of glioma patients [ 39 ]. This corroborates the findings of our work to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…ATP6AP1 gene mutations are involved in congenital disorders of glycosylation (CDG) and affect multiple organ systems, including immunodeficiency and cognitive impairment [ 36 , 37 , 38 ]. One study recently showed that a risk signature including ATP6AP1 could reasonably predict the prognosis and immune microenvironment of glioma patients [ 39 ]. This corroborates the findings of our work to some extent.…”
Section: Discussionmentioning
confidence: 99%
“… 158 One research report that the rate of immune cell infiltration (M1 macrophages, neutrophils, CD103 cells and NK cells) is high, and the antitumor effectors (iNOS, INF‐γ, IL‐1α) are enhanced after using the inhibitor of V‐ATPase. 159 At the same time, the number of cancer cell‐positive cells and the activity of caspase are all decreased. 155 The role of PPIs is exactly similar to the inhibitor of V‐ATPase in suppressing the progression of the tumours.…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 98%
“…The activated caspase‐3 cleaves the corresponding cytoplasmic and nuclear substrates, resulting in the apoptosis of the tumour finally 158 . One research report that the rate of immune cell infiltration (M1 macrophages, neutrophils, CD103 cells and NK cells) is high, and the antitumor effectors (iNOS, INF‐γ, IL‐1α) are enhanced after using the inhibitor of V‐ATPase 159 . At the same time, the number of cancer cell‐positive cells and the activity of caspase are all decreased 155 .…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%
“…[12] In addition, Li et al found that silencing ITGB1 in the cells of non-small cell lung cancer inhibited Yes-associated protein 1 (YAP1) expression, and induced epithelial mesenchymal transition (EMT) and radioresistance. [13] Previous studies have shown that ITGB2 can predict the prognosis of ovarian cancer and glioma, [14,15] ITGB3 is a signature gene that regulates the tumor microenvironment in endometrial cancer, [16] ITGB4 plays an oncogenic role in different cancers [17] , ITGB5 and ITGB6 may be involved in the occurrence of pancreatic cancer [18,19] , ITGB7 may be involved in the regulation of immune microenvironment in glioma, [20] ITGB8 is associated with poor prognosis in patients with high-grade serous ovarian cancer. [21] However, the role of the ITGB gene superfamily in patients with HCC has remained poorly understood.…”
Section: This Research Was Partly Supported By Professor Tao Peng Wit...mentioning
confidence: 99%